Perovskite intermediate powder and method for preparing perovskite solar cell from perovskite intermediate powder

The use of N-formylmorpholine and ethers/esters in a room temperature diffusion process for preparing perovskite intermediate powder addresses the environmental and stability issues of traditional solvents, enhancing the efficiency and scalability of perovskite solar cells.

CN119221121APending Publication Date: 2024-12-31NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411406085.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The traditional preparation of perovskite solar cells using toxic solvents like DMF leads to environmental pollution and health hazards, and the precursor solutions are unstable, making large-scale manufacturing challenging due to narrow processing windows and short storage times.

Method used

A perovskite intermediate powder is prepared using N-formylmorpholine as a ligand and ethers or esters as extraction solvents through a room temperature diffusion method, resulting in a stable perovskite solar cell suitable for large-scale production.

Benefits of technology

The method improves the stability and storage time of perovskite intermediate powder, enhances crystallization quality, and increases photoelectric conversion efficiency, facilitating large-scale production while avoiding environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221121A_ABST
    Figure CN119221121A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of perovskite solar cells, and particularly discloses perovskite intermediate powder and a method for preparing a perovskite solar cell from the perovskite intermediate powder, and the intermediate powder is prepared by using a ligand and an extraction solvent; the preparation method comprises the following steps: performing crystal growth at room temperature in an extraction solvent diffusion manner to obtain a perovskite intermediate by taking N-formyl morpholine as a ligand and an ether or ester solvent and a mixed solvent thereof as an extraction solvent, and then performing low-temperature drying to obtain perovskite intermediate powder. According to the invention, N-formyl morpholine is selected to replace toxic DMF and DMSO, and a perovskite intermediate is dissolved in green solvents such as ethanol, gamma-valerolactone, 2-pentanol and the like to prepare the perovskite thin film. The prepared intermediate powder has relatively long storage stability, and the storage time of perovskite and the stability of a battery device are improved while the solvent toxicity is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a perovskite intermediate powder and a method for preparing a perovskite solar cell using the same. Background Art

[0002] Organic-inorganic hybrid halide perovskite solar cells have received extensive attention from researchers due to their excellent optoelectronic properties such as adjustable band gap, high optical absorption coefficient, and low exciton binding energy. After more than a decade of development, their certified photoelectric conversion efficiency has been greatly improved from the initial 3.8% to the current 26.1%, showing a bright commercial prospect.

[0003] The preparation of high-quality perovskite films is an important step in obtaining high-performance perovskite solar cells. This step is usually prepared by low-temperature solution processing. The choice of solvent is crucial to the film formation process and film quality of perovskite. Traditionally, a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) is usually used as a precursor solvent. In this method, the perovskite precursor is usually dissolved in an organic solvent to form a solution of appropriate concentration; then, the precursor solution is spin-coated into a film, and the extraction solvent is added dropwise during the rotation process to form an intermediate phase film; finally, the intermediate phase is annealed to volatilize the embedded solvent in the intermediate phase, thereby converting the intermediate phase into a perovskite film. However, the large-scale use of the toxic solvent DMF not only causes environmental pollution, but also harms the health of the experimenters. Moreover, the precursor solution prepared by this traditional solvent system is greatly affected by the hydrolysis of DMF and the reaction between perovskite precursor cations, and has a very short storage time, which is not convenient and practical for large-scale manufacturing. At the same time, the membrane preparation method requires accurate dripping of the extraction solvent, has a narrow processing window, and is not conducive to large-scale preparation.

[0004] Although the green solvents commonly used at present have achieved green replacement of solvents, their photoelectric conversion efficiency is unsatisfactory and they cannot achieve a wide crystallization window and high storage stability. Summary of the invention

[0005] In order to solve the technical problems existing in the above-mentioned background technology, the present invention provides a perovskite intermediate powder and a method for preparing a perovskite solar cell therefrom. The present invention uses N-formylmorpholine (NFM) as a ligand of the perovskite intermediate, uses one or more of ethers and esters as extraction solvents, and prepares the perovskite intermediate powder by a room temperature diffusion method, thereby preparing an efficient and stable perovskite solar cell, which is conducive to meeting the needs of large-scale production.

[0006] To achieve the above purpose, the technical solution specifically adopted by the present invention is as follows: A first aspect of the present invention provides a perovskite intermediate powder, wherein the intermediate powder is composed of a perovskite precursor and a ligand, wherein the ligand is N-formylmorpholine.

[0007] As a further illustration of the present invention, the molar ratio of the perovskite precursor to the ligand is 1:1.

[0008] As a further illustration of the present invention, the perovskite precursor includes lead halide and an organic amine salt, wherein the lead halide is selected from at least one of PbI2 and PbBr2; the organic amine salt is selected from at least one of formamidinium iodide, formamidinium iodide, formamidinium bromide, methylamine chloride, methylamine iodine, methylamine bromide, and cesium iodide.

[0009] A second aspect of the present invention provides a method for preparing a perovskite intermediate powder, the method comprising the following steps: Step 1: dissolving the perovskite precursor in an N-formylmorpholine solution, heating and dissolving, and filtering to obtain a mixed solution with a concentration of 0.5-2M; Step 2: Under room temperature, using an extraction solvent to perform ligand diffusion extraction on the mixed solution obtained in step 1, so as to crystallize the mixed solution and obtain perovskite intermediate crystals; Step 3: Drying the perovskite intermediate crystals to remove the remaining ligands to obtain perovskite intermediate powder.

[0010] As a further illustration of the present invention, in step 1, an organic filter head is used for filtration.

[0011] As a further illustration of the present invention, the extraction solvent is one of an ether or ester solvent, or a mixed solvent of ethers and esters, and the mixed volume ratio of ether to ester solvents is 20:1-5:1; wherein the ether solvent is at least one of isopropyl ether, anisole, and ethyl ether, and / or the ester solvent is at least one of methyl acetate, ethyl acetate, and butyl acetate.

[0012] As a further illustration of the present invention, the diffusion extraction process of step 2 specifically includes the following process: Step 201: putting the mixed solution obtained in step 1 into a transparent vial and leaving it open for later use; Step 202: Place the extraction solvent in a large transparent bottle, then place the small transparent bottle obtained in step 201 into the large transparent bottle containing the extraction solvent, seal the large transparent bottle and place it at room temperature to diffuse the extraction solvent to obtain perovskite intermediate crystals.

[0013] As a further illustration of the present invention, in step 202, the diffusion time of the extraction solvent is 4 h-72 h.

[0014] As a further illustration of the present invention, the molar ratio of the perovskite precursor to the ligand in the perovskite intermediate crystal is 1:1.

[0015] As a further illustration of the present invention, the drying process in step 3 is: placing the perovskite intermediate crystal in an oven at 25-50° C. for low-temperature drying.

[0016] As a further illustration of the present invention, in step 3, the perovskite intermediate crystals need to be ground after drying to obtain the perovskite intermediate powder.

[0017] A third aspect of the present invention provides a method for preparing a perovskite solar cell, the method comprising the following steps: Step 1: Take the above-mentioned perovskite intermediate powder or the perovskite intermediate powder prepared by the above-mentioned method, dissolve it in a green solvent to obtain a perovskite precursor solution; Step 2: using the perovskite precursor solution obtained in step 1 to prepare a perovskite film on a substrate covered with an electron transport layer, and after heat treatment, forming a perovskite light absorption layer on the substrate; Step 3: spin-coating a hole transport layer on the perovskite light-absorbing layer, and evaporating a metal electrode on the hole transport layer to obtain a perovskite solar cell.

[0018] As a further illustration of the present invention, in step 1, the preparation process of the perovskite precursor solution is specifically as follows: The above-mentioned perovskite intermediate powder or the perovskite intermediate powder prepared by the above-mentioned method is dissolved in a green solvent, heated and stirred for 2-24 h at a temperature of 25-100 ° C to obtain a perovskite precursor solution with a concentration of 0.5-2M; wherein the green solvent is any one of ethanol, γ-valerolactone, and 2-pentanol.

[0019] As a further illustration of the present invention, the substrate is preferably a conductive glass substrate.

[0020] As a further illustration of the present invention, in step 2, the perovskite film is prepared by spin coating, scraping or immersion, the heat treatment temperature is 100-150° C., and the heat treatment time is 10-60 min.

[0021] As a further illustration of the present invention, the perovskite solar cell prepared by the above method includes a conductive glass layer, an electron transport layer, a perovskite light absorbing layer, a hole transport layer, and a back electrode in sequence; wherein the conductive glass layer is preferably FTO; the electron transport layer is one of TiO2 or SnO2; the hole transport layer is Spiro-OMeTAD; and the back electrode is one of Ag or Au.

[0022] Compared with the prior art, the present invention has the following beneficial technical effects: 1. The ligand N-formylmorpholine used in the present invention has better thermal stability and more excellent chemical properties, and can produce a stronger effect with the organic cations in the perovskite precursor, thereby improving the stability of the perovskite intermediate powder, thereby improving the storage time and device repeatability of the perovskite intermediate powder and the perovskite precursor solution, which is more beneficial for application in large-scale production and avoids the waste of residual solution and environmental pollution.

[0023] 2. The perovskite intermediate powder of the present invention is composed of a perovskite precursor and a ligand in a molar ratio of 1:1. The ligand and the precursor are bonded by hydrogen bonds, and the ligand N-formylmorpholine is easier to remove from the intermediate, thereby avoiding the breakage of high-energy chemical bonds, achieving a crystallization mode of fast nucleation and slow growth, and being easier to form a thin film with fewer defects, thereby improving the crystallization quality of the thin film, and further improving the photoelectric conversion efficiency and stability of the device.

[0024] 3. The room temperature diffusion process used in the present invention to prepare the perovskite intermediate powder avoids the problem of narrow processing window of the extraction solvent and has the prospect of large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of the structure of a perovskite solar cell prepared by the present invention; Figure 2 The process flow of the perovskite intermediate powder prepared by the present invention; Figure 3 3 (b) is the XRD spectrum of the perovskite intermediate single crystal prepared in Example 1; 3 (b) is the XRD spectrum of the perovskite powder prepared in Example 1; Figure 4 (a) is the XRD spectrum of the perovskite intermediate single crystal prepared in Example 2, and 4 (b) is the XRD spectrum of the perovskite powder prepared in Example 2; Figure 5 (a) is the XRD spectrum of the perovskite intermediate powder prepared in Example 3 after direct heating, Figure 5 (b) is the XRD spectrum of the perovskite film prepared from the perovskite intermediate powder prepared in Example 3; Figure 6 (a) is a current-voltage curve of the perovskite solar cell prepared in Example 4; Figure 6 (b) is a SEM image of the perovskite film prepared in Example 4; Figure 7 (a) is a current-voltage curve of the perovskite solar cell prepared in Example 5; Figure 7(b) is a SEM image of the perovskite film prepared in Example 5; Figure 8 (a) is a current-voltage curve of the perovskite solar cell prepared in Example 6; Figure 8 (b) is a SEM image of the perovskite film prepared in Example 6; Fig. 9 It is a normalized curve of the photoelectric conversion efficiency of the perovskite solar cell prepared in Example 6 and the perovskite solar cell prepared in Comparative Example 1 after being placed under environmental conditions for different days; Fig.10 It is a normalized curve of the photoelectric conversion efficiency of the perovskite solar cell prepared in Example 7 and the perovskite solar cell prepared in Comparative Example 2; Fig.11 This is a current-voltage curve of the perovskite solar cell prepared in Comparative Example 1. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The invention provides a perovskite intermediate powder. The intermediate powder consists of a perovskite precursor and a ligand, wherein the ligand is N-formylmorpholine.

[0028] Further, the molar ratio of the perovskite precursor to the ligand is 1: 1. The perovskite precursor includes lead halide and an organic amine salt, wherein the lead halide is selected from at least one of PbI2 and PbBr2; the organic amine salt is selected from at least one of formamidinium iodide, formamidinium iodide, formamidinium bromide, methylamine chloride, methylamine iodide, methylamine bromide, and cesium iodide.

[0029] like Figure 2 As shown, the method for preparing the above-mentioned perovskite intermediate powder comprises the following steps: Step 1: Dissolve the perovskite precursor in N-formylmorpholine solution, heat to dissolve, and filter to obtain a mixed solution with a concentration of 0.5-2M.

[0030] Furthermore, it is preferred to use an organic filter head for filtration, and the concentration of the mixed solution can be, for example, 0.5M, 0.7M, 1M, 1.2M, 1.5M, 1.7M, 2M, etc.

[0031] Step 2: Under room temperature, use an extraction solvent to perform ligand diffusion extraction on the mixed solution obtained in step 1 to crystallize the mixed solution to obtain perovskite intermediate crystals; Further, the extraction solvent is one of ether or ester solvents, or a mixed solvent of ether and ester, and the mixed volume ratio of ether to ester solvent is 20:1-5:1, for example, 20:1, 18:1, 15:1, 13:1, 10:1, 8:1, 5:1, etc. Among them, the ether solvent is at least one of isopropyl ether, anisole, and ethyl ether, and / or the ester solvent is at least one of methyl acetate, ethyl acetate, and butyl acetate.

[0032] The above diffusion extraction process specifically includes the following processes: Step 201: putting the mixed solution obtained in step 1 into a transparent vial and leaving it open for later use; Step 202: Place the extraction solvent in a large transparent bottle, then place the small transparent bottle obtained in step 201 into the large transparent bottle containing the extraction solvent, seal the large transparent bottle and place it at room temperature to diffuse the extraction solvent to obtain perovskite intermediate crystals.

[0033] Furthermore, the diffusion time of the above-mentioned extraction solvent is 4 h-72 h, for example, it can be 4 h, 12 h, 24 h, 36 h, 48 h, 60 h, 72 h, etc.

[0034] Step 3: Dry the perovskite intermediate crystals to remove the remaining ligands to obtain perovskite intermediate powder.

[0035] Furthermore, the molar ratio of the perovskite precursor to the ligand in the perovskite intermediate crystal is 1:1.

[0036] Furthermore, the above drying process is as follows: placing the perovskite intermediate crystals in an oven at 25-50° C. for low-temperature drying.

[0037] Furthermore, in step 3, the perovskite intermediate crystals are dried and then ground to obtain perovskite intermediate powder.

[0038] The present invention also provides a method for preparing a perovskite solar cell, comprising the following steps: Step 1: Take the above-mentioned perovskite intermediate powder or the perovskite intermediate powder prepared by the above-mentioned method, dissolve it in a green solvent, and obtain a perovskite precursor solution.

[0039] Specifically, the preparation process of the perovskite precursor solution is as follows: The above-mentioned perovskite intermediate powder or the perovskite intermediate powder prepared by the above-mentioned method is dissolved in a green solvent, heated and stirred for 2-24 h at a temperature of 25-100 ° C to obtain a perovskite precursor solution with a concentration of 0.5-2 M; wherein the green solvent is any one of ethanol, γ-valerolactone, and 2-pentanol.

[0040] Furthermore, the dissolution temperature may be, for example, 25°C, 35°C, 45°C, 55°C, 65°C, 75°C, 85°C, 100°C, etc.; the stirring time may be, for example, 2 h, 5 h, 10 h, 12 h, 15 h, 20 h, 24 h, etc. The concentration of the perovskite precursor solution may be, for example, 0.5M, 0.7M, 1M, 1.2M, 1.5M, 1.7M, 2M, etc.

[0041] Step 2: The perovskite precursor solution obtained in step 1 is used to prepare a perovskite film on a substrate covered with an electron transport layer, and after heat treatment, a perovskite light absorbing layer is formed on the substrate.

[0042] The substrate is preferably a conductive glass substrate.

[0043] Preferably, the perovskite film is prepared by spin coating, scraping or immersion, and the heat treatment temperature is 100-150° C. and the heat treatment time is 10-60 min.

[0044] Furthermore, the temperature of the heat treatment may be, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc.; the time of the heat treatment may be, for example, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, etc.

[0045] Furthermore, the thickness of the perovskite light absorbing layer is 300-800 nm, for example, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, etc.

[0046] Step 3: Spin-coat a hole transport layer on the perovskite light-absorbing layer, and evaporate a metal electrode on the hole transport layer to obtain a perovskite solar cell.

[0047] like Figure 1 As shown, the perovskite solar cell prepared by the above method includes a conductive glass layer, an electron transport layer, a perovskite light absorbing layer, a hole transport layer, and a back electrode in sequence; wherein the conductive glass layer is preferably FTO; the electron transport layer is one of TiO2 or SnO2; the hole transport layer is Spiro-OMeTAD; and the back electrode is one of Ag or Au.

[0048] Among them, the preparation process of the TiO2 electron transport layer is the CBD chemical water bath deposition method, the hydrothermal temperature is 50-90°C, and the annealing temperature is 90-150°C; the preparation process of the SnO2 electron transport layer is a spin coating process, specifically, the process parameters of SnO2 are: rotation speed 1000-4000 rpm / min; annealing process parameters are: annealing temperature 80-150°C.

[0049] The preparation process of the Spiro-OMeTAD hole transport layer is a spin coating process. Specifically, the process parameters of the spin coating of Spiro-OMeTAD are: a rotation speed of 2000 to 6000 rpm / min and a time of 10 to 30 s.

[0050] The technical solution of the present invention is further explained below in conjunction with specific embodiments and comparative examples. Example 1

[0051] In this embodiment, the extraction solvent is ethyl acetate and the ligand is N-formylmorpholine; The perovskite precursor raw materials are FAI and PbI2.

[0052] S1: Prepare the perovskite precursor solution: dissolve FAI and PbI2 in N-formylmorpholine solution at a molar ratio of 1:1, heat to dissolve, and filter through an organic filter head to obtain a mixed solution with a concentration of 1.2M; S2: Take 400 μl of the prepared solution and put it into a 3 ml transparent sample bottle and leave it open for use. Add 2 ml of ethyl acetate into a 20 ml transparent sample bottle, put the 3 ml sample bottle into the 20 ml sample bottle, tighten the bottle cap and seal it with sealing film, and place it at room temperature to diffuse the extraction solvent. S3: After 2 days, the grown light yellow crystals are taken out and placed in an oven at 45°C for 24 hours. After grinding, a light yellow powder is obtained, which is the perovskite intermediate powder.

[0053] Figure 3 (a) is the XRD pattern of the perovskite intermediate single crystal, and 3 (b) is the XRD pattern of the perovskite powder. Example 2

[0054] In this embodiment, the extraction solvent is ethyl acetate and the ligand is N-formylmorpholine; The perovskite precursor raw materials are MAI and PbI2.

[0055] S1: Prepare the perovskite precursor solution: dissolve MAI and PbI2 in N-formylmorpholine solution at a molar ratio of 1:1, heat to dissolve, and filter through an organic filter head to obtain a mixed solution with a concentration of 1.2M; S2: Take 400 μl of the prepared solution and put it into a 3 ml transparent sample bottle and leave it open for use. Add 2 ml of ethyl acetate into a 20 ml transparent sample bottle, put the 3 ml sample bottle into the 20 ml sample bottle, tighten the bottle cap and seal it with sealing film, and place it at room temperature for extraction solvent diffusion; S3: After 2 days, the grown light yellow crystals are taken out and placed in an oven at 45°C for 24 hours. After grinding, a light yellow powder is obtained, which is the perovskite intermediate powder.

[0056] Figure 4 (a) is the XRD pattern of the perovskite intermediate single crystal, and 4 (b) is the XRD pattern of the perovskite powder. Example 3

[0057] In this embodiment, the extraction solvent is isopropyl ether and the ligand is N-formylmorpholine; The perovskite precursor raw materials are MABr, PbBr2, MACl, FAI and PbI2.

[0058] S1: Prepare the perovskite precursor solution: dissolve MABr, PbBr2, FAI and PbI2 in N-formylmorpholine solution at a molar ratio of 0.05:0.05:0.95:1.007, add 20% MACl, stir at 55 °C for 1 h, and filter through an organic filter to obtain a mixed solution with a concentration of 1.2 M; S2: Take 400 μl of the prepared solution and put it into a 3 ml transparent sample bottle and leave it open for use. Add 2 ml of ethyl acetate into a 20 ml transparent sample bottle, put the 3 ml sample bottle into the 20 ml sample bottle, tighten the bottle cap and seal it with sealing film, and place it at room temperature for extraction solvent diffusion; S3: After 2 days, the grown light yellow crystals are taken out and placed in an oven at 45°C for 24 hours. After grinding, a light yellow powder is obtained, which is the perovskite intermediate powder.

[0059] S4: The prepared perovskite intermediate powder was dissolved in ethanol, the spin coating speed was 6000 rpm / min, the spin coating time was 30s, and the perovskite film was obtained after annealing at 150 °C for 10 min; Figure 5 (a) is the XRD pattern of the intermediate powder after direct heating. Figure 5 (b) XRD spectrum of the intermediate powder after preparing the perovskite film. Example 4

[0060] In this embodiment, the extraction solvent is ethyl acetate and the ligand is N-formylmorpholine; The raw materials of perovskite precursor are FAI and PbI2. The preparation steps of perovskite solar cells are as follows: S1: Cleaning of conductive glass substrate: The purchased FTO glass was ultrasonically treated with deionized water, acetone, and anhydrous ethanol in sequence for 30 min to clean the glass surface, and then dried with nitrogen for later use; S2: Preparation of electron transport layer: After the FTO glass is placed in UV ozone for 15 minutes, TiO2 is deposited on the FTO glass using the CBD chemical water bath deposition method. First, the glass cleaned by UVO is placed in a petri dish for standby use, 850 μl of TiCl4 solution is slowly dripped into a vial containing 40 ml of ultrapure water after freezing, and after the ice is completely melted, it is poured into the petri dish, and placed in a 70°C oven for hydrothermal treatment for 50 min, and then the residual TiCl4 on the surface is cleaned and placed in a 150°C oven for annealing for 1h to obtain TiO2.

[0061] S3: preparing a perovskite light-absorbing layer: dissolving the perovskite intermediate powder obtained in Example 1 in ethanol, spinning at a speed of 6000 rpm / min for 30 seconds, and annealing at 150° C. for 10 minutes to obtain a perovskite film; S4: Preparation of hole transport layer: After the chlorobenzene solution of the hole transport material Spiro-OMeTAD is fully mixed, 25 μl is added dropwise onto the perovskite film at a spin coating speed of 4000 rpm / min for 30 s to obtain a hole transport layer; S5: Preparation of metal electrode layer: Using thermal evaporation method, 80 nm of silver is evaporated on the hole transport layer.

[0062] The prepared perovskite solar cell was tested for performance, and its photoelectric conversion efficiency reached 20.77%; Figure 6 (a) is a current-voltage curve of the perovskite solar cell prepared in Example 4; Figure 6 (b) is the SEM image of the perovskite film prepared in Example 4. Example 5

[0063] In this embodiment, the extraction solvent is ethyl acetate and the ligand is N-formylmorpholine; The raw materials of perovskite precursor are MABr, PbBr2, MACl, FAI and PbI2. The preparation steps of perovskite solar cells are as follows: S1: Cleaning of conductive glass substrate: The purchased FTO glass was ultrasonically treated with deionized water, acetone, and anhydrous ethanol in sequence for 30 min to clean the glass surface, and then dried with nitrogen for later use; S2: Preparation of electron transport layer: After the FTO glass is placed in UV ozone for 15 minutes, TiO2 is deposited on the FTO glass using the CBD chemical water bath deposition method. First, the glass cleaned by UVO is placed in a petri dish for standby use, 850 μl of TiCl4 solution is slowly dripped into a vial containing 40 ml of ultrapure water after freezing, and after the ice is completely melted, it is poured into the petri dish, and placed in a 70°C oven for hydrothermal treatment for 50 min, and then the residual TiCl4 on the surface is cleaned and placed in a 150°C oven for annealing for 1h to obtain TiO2.

[0064] S3: preparing a perovskite light-absorbing layer: dissolving the perovskite intermediate powder obtained in Example 3 in ethanol, spinning at a speed of 5000 rpm / min for 30 seconds, and annealing at 150° C. for 10 minutes to obtain a perovskite film; S4: Preparation of hole transport layer: After the chlorobenzene solution of the hole transport material Spiro-OMeTAD is fully mixed, 25 μl is added dropwise onto the perovskite film at a spin coating speed of 4000 rpm / min for 30 s to obtain a hole transport layer; S5: Preparation of metal electrode layer: Using thermal evaporation method, 80 nm of silver is evaporated on the hole transport layer.

[0065] The prepared perovskite solar cell was tested for performance, and its photoelectric conversion efficiency reached 21.41%; Figure 7 (a) is a current-voltage curve of the perovskite solar cell prepared in Example 5; Figure 7 (b) is the SEM image of the perovskite film prepared in Example 5. Example 6

[0066] In this embodiment, the extraction solvent is butyl acetate and the ligand is N-formylmorpholine; The raw materials of perovskite precursor are MABr, PbBr2, MACl, FAI and PbI2. The preparation steps of perovskite solar cells are as follows: S1: Cleaning of conductive glass substrate: The purchased FTO glass was ultrasonically treated with deionized water, acetone, and anhydrous ethanol in sequence for 30 min to clean the glass surface, and then dried with nitrogen for later use; S2: Preparation of electron transport layer: After the FTO glass is placed in UV ozone for 15 minutes, TiO2 is deposited on the FTO glass using the CBD chemical water bath deposition method. First, the glass cleaned by UVO is placed in a petri dish for standby use, 850 μl of TiCl4 solution is slowly dripped into a vial containing 40 ml of ultrapure water after freezing, and after the ice is completely melted, it is poured into the petri dish, and placed in a 70°C oven for hydrothermal treatment for 50 min, and then the residual TiCl4 on the surface is cleaned and placed in a 150°C oven for annealing for 1h to obtain TiO2.

[0067] S3: preparing a perovskite light-absorbing layer: dissolving the perovskite intermediate powder obtained in Example 3 in anhydrous ethanol, spinning at a speed of 6000 rpm / min for 30 seconds, and annealing at 150° C. for 10 minutes to obtain a perovskite film; S4: Preparation of hole transport layer: After the chlorobenzene solution of the hole transport material Spiro-OMeTAD is fully mixed, 25 μl is added dropwise onto the perovskite film at a spin coating speed of 4000 rpm / min for 30 s to obtain a hole transport layer; S5: Preparation of metal electrode layer: Using thermal evaporation method, 80 nm of silver is evaporated on the hole transport layer.

[0068] The prepared perovskite solar cell was tested for performance, and its photoelectric conversion efficiency reached 22.53%; Figure 8 (a) is a current-voltage curve of the perovskite solar cell prepared in Example 6; Figure 8 (b) is a SEM image of the perovskite film prepared in Example 6. Fig. 9 As shown, compared with Comparative Example 1, Example 6 has better stability. Example 7

[0069] In this embodiment, the extraction solvent is butyl acetate:isopropyl ether = 9:1, and the ligand is N-formylmorpholine; The raw materials of perovskite precursor are MABr, PbBr2, MACl, FAI and PbI2. The preparation steps of perovskite solar cells are as follows: S1: Cleaning of conductive glass substrate: The purchased FTO glass was ultrasonically treated with deionized water, acetone, and anhydrous ethanol in sequence for 30 min to clean the glass surface, and then dried with nitrogen for later use; S2: Preparation of electron transport layer: After the FTO glass is placed in UV ozone for 15 minutes, TiO2 is deposited on the FTO glass using the CBD chemical water bath deposition method. First, the glass cleaned by UVO is placed in a petri dish for standby use, 850 μl of TiCl4 solution is slowly dripped into a vial containing 40 ml of ultrapure water after freezing, and after the ice is completely melted, it is poured into the petri dish, and placed in a 70°C oven for hydrothermal treatment for 50 min, and then the residual TiCl4 on the surface is cleaned and placed in a 150°C oven for annealing for 1h to obtain TiO2.

[0070] S3: preparing a perovskite light-absorbing layer: the perovskite intermediate powder obtained in Example 3 was placed for 6 days, 9 days, 15 days, 21 days and 32 days respectively, then dissolved in ethanol, the spin coating speed was 6000 rpm / min, the spin coating time was 30 s, and the perovskite film was annealed at 150 °C for 10 min to obtain a perovskite film; S4: Preparation of hole transport layer: After the chlorobenzene solution of the hole transport material Spiro-OMeTAD is fully mixed, 25 μl is added dropwise onto the perovskite film at a spin coating speed of 4000 rpm / min for 30 s to obtain a hole transport layer; S5: Preparation of metal electrode layer: Using thermal evaporation method, 80 nm of silver is evaporated on the hole transport layer.

[0071] The prepared perovskite solar cell was subjected to performance testing, and the measured photoelectric conversion efficiency was normalized and plotted, as shown in Fig.10 As shown, compared with Comparative Example 2, Example 7 has better storage stability.

[0072] Comparative Example 1 Fabrication of perovskite solar cells using the traditional precursor solvent DMF:DMSO.

[0073] The raw materials for forming the perovskite light-absorbing layer are MABr, PbBr2, MACl, FAI and PbI2.

[0074] S1: Cleaning of conductive glass substrate: The purchased FTO glass was ultrasonically treated with deionized water, acetone, and anhydrous ethanol in sequence for 30 min to clean the glass surface, and then dried with nitrogen for later use; S2: Preparation of electron transport layer: After the FTO glass is placed in UV ozone for 15 minutes, TiO2 is deposited on the FTO glass using the CBD chemical water bath deposition method. First, the glass cleaned by UVO is placed in a petri dish for standby use, 850 μl of TiCl4 solution is slowly dripped into a vial containing 40 ml of ultrapure water after freezing, and after the ice is completely melted, it is poured into the petri dish, and placed in a 70 ℃ oven for hydrothermal treatment for 50 min, and then the residual TiCl4 on the surface is cleaned and placed in a 150 ℃ oven for annealing for 1h to obtain TiO2.

[0075] S3: Prepare the perovskite precursor solution: dissolve MABr, PbBr2, FAI and PbI2 in a mixed solution of DMF:DMSO=8:1 at a molar ratio of 0.05:0.05:0.95:1.007, stir at 55 °C for 2 h, and filter through an organic filter to obtain a perovskite precursor solution with a concentration of 1.5 M; S4: Preparation of perovskite light-absorbing layer: 40 μl of perovskite precursor solution was dripped on a conductive glass substrate covered with an electron transport layer, and then spin-coated in two steps. The first step was at a speed of 1000 rpm / min and a time of 10 s. The second step was at a speed of 5000 rpm / min and a time of 30 s. In the last 10 s before the end of spin coating, 150 μl of ethyl acetate was dripped. After the spin coating was completed, the perovskite film was annealed at 150 °C for 10 min to obtain the perovskite film. S5: Preparation of hole transport layer: After the chlorobenzene solution of the hole transport material Spiro-OMeTAD is fully mixed, 25 μl is added dropwise onto the perovskite film at a spin coating speed of 4000 rpm / min for 30 s to obtain a hole transport layer; S6: Prepare the metal electrode layer: Use thermal evaporation to evaporate 80 nm of silver on the hole transport layer.

[0076] The prepared perovskite solar cell was tested for performance, and its photoelectric conversion efficiency was 21.45%; Fig.11 The current-voltage curve of the perovskite solar cell prepared in Comparative Example 1 shows that the efficiency of the comparative example is lower than that of Example 6. Fig. 9 As shown, compared with Example 6, the stability of Comparative Example 1 is poor.

[0077] Comparative Example 2: Fabrication of perovskite solar cells using the traditional precursor solvent DMF:DMSO.

[0078] The raw materials for forming the perovskite light-absorbing layer are MABr, PbBr2, MACl, FAI and PbI2.

[0079] S1: Prepare perovskite precursor solution: dissolve MABr, PbBr2, FAI and PbI2 in a mixed solution of DMF:DMSO=8:1 at a molar ratio of 0.05:0.05:0.95:1.007, stir at 55 °C for 2 h, and filter through an organic filter to obtain a perovskite precursor solution with a concentration of 1.5 M; place the prepared perovskite solution in a nitrogen atmosphere away from light for 1 day, 6 days, 9 days, and 15 days respectively; The following steps were repeated for different number of days after the perovskite precursor solution was left to stand: S2: Cleaning of conductive glass substrate: The purchased FTO glass was ultrasonically treated with deionized water, acetone, and anhydrous ethanol in sequence for 30 min to clean the glass surface, and then dried with nitrogen for later use; S3: Preparation of electron transport layer: After the FTO glass is placed in UV ozone for 15 minutes, TiO2 is deposited on the FTO glass using the CBD chemical water bath deposition method. First, the glass cleaned by UVO is placed in a petri dish for standby use, 850 μl of TiCl4 solution is slowly dripped into a vial containing 40 ml of ultrapure water after freezing, and after the ice is completely melted, it is poured into the petri dish, and placed in a 70 ℃ oven for hydrothermal treatment for 50 min, and then the residual TiCl4 on the surface is cleaned and placed in a 150 ℃ oven for annealing for 1h to obtain TiO2.

[0080] S4: Preparation of perovskite light-absorbing layer: 40 μl of perovskite precursor solution was dripped on a conductive glass substrate covered with an electron transport layer, and then spin-coated in two steps. The first step was at a speed of 1000 rpm / min and a time of 10 s. The second step was at a speed of 5000 rpm / min and a time of 30 s. In the last 10 s before the end of spin coating, 150 μl of ethyl acetate was dripped. After the spin coating was completed, the perovskite film was annealed at 150 °C for 10 min to obtain the perovskite film. S5: Preparation of hole transport layer: After the chlorobenzene solution of the hole transport material Spiro-OMeTAD is fully mixed, 25 μl is added dropwise onto the perovskite film at a spin coating speed of 4000 rpm / min for 30 s to obtain a hole transport layer; S6: Prepare the metal electrode layer: Use thermal evaporation to evaporate 80 nm of silver on the hole transport layer.

[0081] like Fig.10 As shown, compared with Example 7, the storage stability of the precursor solution of Comparative Example 2 is worse.

[0082] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A perovskite intermediate powder, characterized in that: The intermediate powder consists of a perovskite precursor and a ligand, wherein the ligand is N-formylmorpholine.

2. The perovskite intermediate powder according to claim 1, characterized in that The molar ratio of the perovskite precursor to the ligand is 1:

1.

3. The perovskite intermediate powder according to claim 1, characterized in that The perovskite precursor includes lead halide and organic amine salt, wherein the lead halide is selected from at least one of PbI2 and PbBr2; the organic amine salt is selected from at least one of formamidinium iodide, formamidinium iodide, formamidinium bromide, methylamine chloride, methylamine iodide, methylamine bromide, and cesium iodide.

4. A method for preparing a perovskite intermediate powder, characterized in that: The method comprises the following steps: Step 1: dissolving the perovskite precursor in an N-formylmorpholine solution, heating and dissolving, and filtering to obtain a mixed solution with a concentration of 0.5-2M; Step 2: Under room temperature, using an extraction solvent to perform ligand diffusion extraction on the mixed solution obtained in step 1, so as to crystallize the mixed solution and obtain perovskite intermediate crystals; Step 3: Drying the perovskite intermediate crystals to remove the remaining ligands to obtain perovskite intermediate powder.

5. The method for preparing the perovskite intermediate powder according to claim 4, characterized in that: The extraction solvent is one of ether or ester solvents, or a mixed solvent of ether and ester, and the mixed volume ratio of ether to ester solvent is 20:1-5:1; wherein, The ether solvent is at least one of isopropyl ether, anisole and ethyl ether, and / or the ester solvent is at least one of methyl acetate, ethyl acetate and butyl acetate.

6. The method for preparing the perovskite intermediate powder according to claim 4, characterized in that: The diffusion extraction process of step 2 specifically includes the following processes: Step 201: putting the mixed solution obtained in step 1 into a transparent vial and leaving it open for later use; Step 202: Place the extraction solvent in a large transparent bottle, then place the small transparent bottle obtained in step 201 into the large transparent bottle containing the extraction solvent, seal the large transparent bottle and place it at room temperature to diffuse the extraction solvent to obtain perovskite intermediate crystals.

7. The method for preparing the perovskite intermediate powder according to claim 4, characterized in that: The molar ratio of the perovskite precursor to the ligand in the perovskite intermediate crystal is 1:

1.

8. A method for preparing a perovskite solar cell, characterized in that: The method comprises the following steps: Step 1: Take the perovskite intermediate powder described in any one of claims 1 to 3 or the perovskite intermediate powder prepared by the method described in any one of claims 4 to 7, and dissolve it in a green solvent to obtain a perovskite precursor solution; Step 2: using the perovskite precursor solution obtained in step 1 to prepare a perovskite film on a substrate covered with an electron transport layer, and after heat treatment, forming a perovskite light absorption layer on the substrate; Step 3: spin-coating a hole transport layer on the perovskite light-absorbing layer, and evaporating a metal electrode on the hole transport layer to obtain a perovskite solar cell.

9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: In step 1, the preparation process of the perovskite precursor solution is specifically as follows: The perovskite intermediate powder according to any one of claims 1 to 3 or the perovskite intermediate powder prepared by the method according to any one of claims 4 to 7 is dissolved in a green solvent, heated and stirred for 2 to 24 h at a temperature of 25 to 100 ° C to obtain a perovskite precursor solution with a concentration of 0.5 to 2 M; wherein the green solvent is any one of ethanol, γ-valerolactone, and 2-pentanol.

10. The method for preparing a perovskite solar cell according to claim 8, wherein: In step 2, the perovskite film is prepared by spin coating, scraping or immersion, the heat treatment temperature is 100-150° C., and the heat treatment time is 10-60 min.